2012
DOI: 10.2214/ajr.10.6057
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoenhancement of Renal Cysts: Influence of Lesion Size, Lesion Location, Slice Thickness, and Number of MDCT Detectors

Abstract: Pseudoenhancement of renal cysts significantly correlates with size smaller than 1 cm and central location. Although pseudoenhancement increases with larger numbers of detectors, the correlation was not statistically significant. Cysts in the 1- to 1.5-cm range have a 19% likelihood of pseudoenhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 24 publications
0
27
0
4
Order By: Relevance
“…Studies have been performed in an attempt to determine the effect of various renal cyst characteristics (e.g., size [27, 1013], unenhanced attenuation [6], and location [6, 11]), CT parameters (e.g., number of detectors [37], tube current [3], peak kilovoltage [5, 11], kernel [3]), and background renal parenchymal attenuation [25, 7, 11–14] on the occurrence of renal cyst pseudoenhancement. However, because of the difficulty in establishing a suitable reference standard to confirm the simple nature of in vivo renal cysts (simple renal cysts typically are not resected), these studies have primarily used ex vivo phantoms to simulate what might occur in an in vivo environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have been performed in an attempt to determine the effect of various renal cyst characteristics (e.g., size [27, 1013], unenhanced attenuation [6], and location [6, 11]), CT parameters (e.g., number of detectors [37], tube current [3], peak kilovoltage [5, 11], kernel [3]), and background renal parenchymal attenuation [25, 7, 11–14] on the occurrence of renal cyst pseudoenhancement. However, because of the difficulty in establishing a suitable reference standard to confirm the simple nature of in vivo renal cysts (simple renal cysts typically are not resected), these studies have primarily used ex vivo phantoms to simulate what might occur in an in vivo environment.…”
mentioning
confidence: 99%
“…However, because of the difficulty in establishing a suitable reference standard to confirm the simple nature of in vivo renal cysts (simple renal cysts typically are not resected), these studies have primarily used ex vivo phantoms to simulate what might occur in an in vivo environment. Although a few in vivo studies have been performed, most of these have been limited by either univariate analysis [10] or a self-referential reference standard (e.g., unenhanced CT characteristics) [6, 11]. Only one other study to our knowledge has incorporated a multivariate analysis using MRI as an in vivo reference standard [7].…”
mentioning
confidence: 99%
“…Partial volume averaging can be mitigated by using thin CT slices to assess the density of a lesion, but thin slices have much higher image noise, and this fact, coupled with the inherently smaller size of the circular ROI that is placed to measure the CT attenuation of these lesions, can potentially result in an erroneously higher CT number. It has been shown that CT examination of renal lesions can erroneously reveal enhancement of up to 50 HU, termed "pseudoenhancement," which can lead to mischaracterization of a cyst as an enhancing renal mass [14]. The degree of pseudoenhancement is inversely related to the size of the renal lesions [14,15].…”
Section: Mri Characterization Of Lesions In Donor Kidneysmentioning
confidence: 99%
“…It has been shown that CT examination of renal lesions can erroneously reveal enhancement of up to 50 HU, termed "pseudoenhancement," which can lead to mischaracterization of a cyst as an enhancing renal mass [14]. The degree of pseudoenhancement is inversely related to the size of the renal lesions [14,15]. This is thought to be the result of the reconstruction algorithm used in helical CT to adjust for beam caused by hardening effects [5].…”
Section: Mri Characterization Of Lesions In Donor Kidneysmentioning
confidence: 99%
“…The phenomenon of pseudo-enhancement is known to be significantly associated with central location and also masses less than 1 cm in size, limiting CT assessment in such cases [54]. When the attenuation change falls within 10–20 HU, subtraction imaging at MRI may be useful if available [55].…”
Section: Synopsis and Synthesis Of Evidencementioning
confidence: 99%